2013
DOI: 10.1073/pnas.1308535110
|View full text |Cite
|
Sign up to set email alerts
|

Huntington disease arises from a combinatory toxicity of polyglutamine and copper binding

Abstract: Huntington disease (HD) is a progressive neurodegenerative disorder caused by dominant polyglutamine (polyQ) expansion within the N terminus of huntingtin (Htt) protein. Abnormal metal accumulation in the striatum of HD patients has been reported for many years, but a causative relationship has not yet been established. Furthermore, if metal is indeed involved in HD, the underlying mechanism needs to be explored. Here using a Drosophila model of HD, wherein Htt exon1 with expanded polyQ (Htt exon1-polyQ) is in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(85 citation statements)
references
References 33 publications
0
85
0
Order By: Relevance
“…281 Modulation of copper homeostasis by genetic and dietary interventions strikingly modifies disease progression in a HTT exon 1 Drosophila model of HD. 282 Copper interaction with mutant HTT promoted toxicity in this model, which was rescued by substituting key copper-coordinating residues, Met8 and His82. 282 The breakdown in metal homeostasis in amyotrophic lateral sclerosis Amyotrophic lateral sclerosis (ALS) is a disease in which motor neurons in the spinal cord and brain progressively deteriorate leading to paralysis and death.…”
Section: Metal Dyshomeostasis In Huntington's Diseasementioning
confidence: 86%
“…281 Modulation of copper homeostasis by genetic and dietary interventions strikingly modifies disease progression in a HTT exon 1 Drosophila model of HD. 282 Copper interaction with mutant HTT promoted toxicity in this model, which was rescued by substituting key copper-coordinating residues, Met8 and His82. 282 The breakdown in metal homeostasis in amyotrophic lateral sclerosis Amyotrophic lateral sclerosis (ALS) is a disease in which motor neurons in the spinal cord and brain progressively deteriorate leading to paralysis and death.…”
Section: Metal Dyshomeostasis In Huntington's Diseasementioning
confidence: 86%
“…Interestingly, copper also alters the activity of glycogen synthase kinase 3β (GSK3β), an enzyme involved in regulating APP processing, linking copper to APP biology through multiple mechanisms (48,49). Additionally, pathological aggregation of both APP and Htt may be mediated by copper binding (50,51). Indeed, Zhou and co-workers showed that when potential copper-binding residues on Htt were mutated, changes in neural copper homeostasis no longer influenced Htt aggregation (51), suggesting that copper levels directly impact HD progression.…”
Section: Copper Signaling In Neurobiologymentioning
confidence: 99%
“…Additionally, pathological aggregation of both APP and Htt may be mediated by copper binding (50,51). Indeed, Zhou and co-workers showed that when potential copper-binding residues on Htt were mutated, changes in neural copper homeostasis no longer influenced Htt aggregation (51), suggesting that copper levels directly impact HD progression. Finally, aggregation of mutant forms of SOD1, an enzyme that requires copper and zinc cofactors for catalytic function, leads to ALS (52,53), and the disease course can be modulated by changes in dietary zinc and copper (54).…”
Section: Copper Signaling In Neurobiologymentioning
confidence: 99%
“…68 Despite this potentially positive role of copper in inducing mutant aggregation, reduction of copper via chelation or via genetic knock-down of copper transporters has mitigated HD pathology in both mouse and fly models of HD while simultaneously reducing aggregation. 69,70 Copper treatment also further decreased the life span of HD flies. 70 These models, however, express only exon1 of the mutant gene, and aggregation may be a necessary step in pathology with these imperfect model systems.…”
Section: Copper and Hdmentioning
confidence: 91%